INTERPRETASI HAKIM, PENGACARA DAN NOTARIS TERHADAP KONSEP HARTA BERSAMA MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI KABUPATEN BANYUMAS (Studi Tentang Kriteria yang Digunakan dalam Mengkualifikasi Harta Bersama) - Subekti, Trusto (Jurnal Dinamika Hukum, 2008)
A marriage always have legal consequences, especially in marriage good together.  Every regulation of that law have the character of abstraction and passive, hence to comprehend content and intention something section in law have to use appliance is so called interprestasi (interpretation method), result of perception (observasi) whereas studied law and regulation, that is as sources of law. This research have the character of research of law with approach of empirical juridis and research type the used is bibliography (research library) field (field of research) to obtain direct explanation of subjek in this research, that is Judges, Lawyers, and Notaries in Sub-Province of Banyumas. Pursuant to research result obtained from 12 (twelve) method interpretation of which can utilized to comprehend community property concept according to article 35 point (1) Act No.l, 1974, in the reality utilized by all law practitioners, only 2 (two) interpretation method, that is interpretation of language 47 (54,65%) and systematic interpretation 29 (45,35%). And result of interpretation inventariasi all practitioners punish to regarding criterion used to determine kualification an object of included in community property from 23 interpretation object item obtained 7 (seven) criterion, as follows: obtained estae during marriage, result of management with diving marriage, production during marriage, earnings during marriage, purchasing during marriage, result of from heritage obtained during marriage, transformation of heritage during marriage. Hence require to be given clear formula pass law and regulation and properly there are same understanding to all practitioners punish to regarding criterion to determine something object of kualification as personal estae or community property, to be society not be bewildered caused by interpretation which different each other. Kata Kunci : Interpretasi, kriteria, konsep harta bersama, hakim pengacara, notaris